THE ARGON FIELD IN ARCADIA, THE SINKHOLE OF NESTANI VILLAGE, GOD POSEIDON AND THE SUBMARINE DINI SPRINGS IN THE ARGOLIC GULF (PELOPONNISOS, GREECE). A GEOMYTHOLOGICAL APPROACH OF THE POSEIDON’S BIRTH. - Mariolakos, I. D.; Mariolakos, D. I. (Bulletin of the Geological Society of Greece, 2004)
The Argon Field (= πεδίο = pedion, in greek) is a small plain in the north part of the much larger Tripolis plain of Central Peloponnisos (Greece). It extends west of Mountain Artemision, which is dedicated to Goddess Artemis (Diana), between Sagas village and that of Nestani, at the province of Manti nia The whole area of Mantinia is well-known since the prehistoric times and, as it is reported by Pausanias, it is mentioned in Greek Mythology. Pausanias (Arcadica, § 7-8) mentions - among others - the following: The word "argon" means "slow cultivation", so that "Argon field" means a field of slow cultivation because of occasional flooding during wintertime, caused by water coming from the surrounding mountains and the karstjc springs flowing from the margins, consisting mainly of multjfokted cretaceous limestones (Ptndos geotectonic unit) The Argon field would have probably turned into a lake, if the water had not been drained through a ground rift. In this case, the rift is apparently the cave - sinkhole of Nestani, which is located at the lowest topographic point of the whole field. After a few days (based on modern tracing experiments) the water reappears from this sinkhole in a submarine system of karstic springs in the Argoltc gulf, that in ancient times were known as Dini, located near Kiveri village. The modern name of the springs is Mikros Anavalos or Aghios Georgios Springs. The subsurface hydraulic communication between the Nestani Sinkhole and Dini springs was known to ancient greeks. According to Greek Mythology when Goddess Rhea, one of the mythical Titans, gave birth to the Greek god Poseidon, she left him near a sheepfold next to a spring, which is known since then as Ama Spring (sheep = αρνί = arni, in greek). Rhea didn’t present the baby, Poseidon, to his father, Cronus, who was another mythical Titan, as she was afraid of him. At that time, Cronus was the head of the Titans, but fearing for a revolt of his children, he was eating them straight after their birth. That is why Rhea told him that she hadn’t given birth to a child, but to a colt (small horse) instead (horse = ίτπτος = hippos, in greek). In this way, Poseidon survived and became one of the most important legendary Gods of the greeks later. A locality is known next to Dini submarine system of kastric springs at the Argolic Gulf, named Genesion or Genethlion (= birthplace), which is considered to be Poseidon’s birthplace. Here, in this place, the ancient inhabitants of Argos used to sacrifice horses, whereas not far away from Nestani, at the small village of Milia, the ruins of a small temple dedicated to Hippios (Horsey) Poseidon have been excavated during the last decades. Poseidon is depicted in many pictures, statues, mosaics etc. In a mosaic, Poseidon comes out from the water on a chariot pulled by four horses. A main question is how Poseidon arrived from a mountainous area to the Argolic Gulf. A geomythological interpretation is that a god such as Poseidon, who was responsible for whatever happened in the water (sea, lakes, ground water etc.) and the earth interior (crust, lithosphère), could not follow a mountainous path, for instance the path over mountain Artemision. On the contrary, for such a god it would be much easier to follow the subsurface water-way through the sinkhole of Nestani village, that is the pathway connected to a subterraneous water flow, which reappears to the surface from the bottom of the sea and in this case to the surface of the Argolic Gulf, through Dini spring. In the case of this myth the hydrogeological conditions of the area are directly connected to the mythological action. This is one more evidence that Poseidon is not a God imported from another culture, but a native one.